Disclosing Strategy in Communicating Uncertainty: Case of Climatology Station Climate Information Dissemination in Lombok Island - I Wayan Suadnya; Agus Purbathin Hadi; Eka Putri Paramita (Soshum: Jurnal Sosial dan Humaniora, 2022)
Certainty of climate information is essential for farmers in developing farming decisions but, climate forecasts produced by Climatology Station contain 30 per cent uncertainty. The fact that climatology station has carried out climate information dissemination to farmers in Lombok. However, many farmers experienced harvesting and planting failure due to climatic uncertainty. The objectives of this research are to describe the communication strategy implemented by the Kediri Climatology Station in communicating climate information to farmers on Lombok Island and to identify obstacles experienced in disseminating climate information. This research was conducted at the Kediri Climatology Station and on the island of Lombok using a descriptive method. Data were collected through in-depth interviews. The collected data were analyzed using descriptive qualitative analysis. The results show that the strategies implemented by the Kediri Climatology Station were strategies to increase the station's credibility through the improvement of data collection technique and analysis to minimize uncertainty, compiling and packaging messages so that farmers easily understand them, conducting direct dissemination through climate field school (SLI) and indirect using media, trying to understand the social and economic conditions of the communicants as well as utilization of feedback. However, there are obstacles faced by the Kediri Climatology Station in providing climate information namely: many extension agents are reluctant to convey climate information to farmers, climate change that affects forecast accuracy, difficulty convincing the public, and lack of funds to conduct Climate Field School, limited personnel, and language barriers.